Russian Federation : 2009 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that the banking system of the Russian Federation is under increasing strain, and private sector credit is contracting. The authorities' response to the crisis has been swift and substantial, driven by concerns that weaknesses in the banking and corporate sectors could lead to a full-fledged crisis. Executive Directors have commended the authorities for a swift and substantial policy response to these developments. Directors have also encouraged the authorities to take a more proactive and concerted approach to tackling the problems in the banking sector.